From automatic integration to selective control: time-resolved effects of sensory cues on numerical comparison - Liang, Xiao; Jiang, Bo; Zhang, Zonghao; Wang, Lijuan (Frontiers in Neuroscience, 2025)
IntroductionApproximate numerical comparison is often influenced by various non-numerical sensory cues, yet whether they act via uniform inhibition (inhibitory control theory) or cue-weighted integration (sensory integration theory) remains debated.MethodsTo clarify this theoretical controversy, the present study tested a cue-specific, temporally staged account by orthogonally manipulating numerosity with a holistic, highweight cue (convex hull) and a basic, lower-weight cue (average dot size) while recording fronto-central ERPs (P2, N450). Twenty-five adults performed a rapid dot array comparison under four congruency conditions.ResultsBehavior showed clear convex-hull dominance: accuracy was high whenever convex hull aligned with numerosity and dropped when it conflicted, regardless of dot-size consistency; response times were unchanged. ERPs revealed a two-stage dynamic: the early P2 selectively tracked dot-size congruency (larger for dot-size–congruent trials), consistent with automatic integration of basic features, whereas the later N450 scaled with conflict structure and cue weight (fully congruent < dot-size–congruent < fully incongruent < convex-hull–congruent/dot-size–incongruent), with no latency differences.DiscussionThese converging results support a time-resolved, weightsensitive mechanism in which basic features bias integration early and holistic configurations dominate later choice and recruit control when misaligned. The account reconciles sensory-integration and inhibitory-control views and motivates further tests of how cue–cue and cue–number conflicts shape numerical decisions.